Knowledge About Early Diagnosis of Breast Cancer, and Breast Cancer Risks Among Syrian Immigrants and Turkish Citizens: A Comparative, Cross-Sectional Study - Kocak, Hatice Serap; Çiçek Gümüş, Ecem; Gümüş, Ecem Çiçek (Galenos Publ House, 2023)
Objective: Cancer affects people regardless of being native or immigrants from developing countries. The most common form of cancer amongst displaced and immigrant women is breast cancer. This study provided a cultural comparison of early diagnosis, screening and breast cancer risks among Syrian immigrants and Turkish citizens in Turkey.Materials and Methods: The study was performed with a descriptive, comparative and cross-sectional design with 589 women (Turkish=302, Syrian=287). A Personal Information Form and Breast Cancer Risk Assessment Form were used for data collection.Results: The knowledge of Syrian immigrant women and behavior regarding breast self-examination, clinical breast examination, and screening with a mammogram were significantly lower than those of Turkish women (p<0.05). In addition, Syrian women's information about general breast cancer early diagnosis and screening was poorer. However, the mean breast cancer risk score was higher in Turkish women (p<0.05).Conclusion: The data highlighted the importance of understanding locally specific barriers to breast cancer screening among immigrants and developing national programs to increase cancer education as a means of prevention.
Knowledge About Early Diagnosis of Breast Cancer, and Breast Cancer Risks Among Syrian Immigrants and Turkish Citizens: A Comparative, Cross-Sectional Study
Keywords: Breast Cancer Risk; Early Diagnosis; Immigrant